Handgrip Strength as a Moderator of the Influence of Age on Olfactory Impairment in Us Adult Population ≥ 40 Years of Age - Garcia-Hermoso, A (Nature Research, 2021)
The aim of this study was to determine whether handgrip strength attenuates the negative relationship between age and olfactory function in a representative US population sample 40 years old and over. A cross-sectional study was performed with 2861 adults from the US National Health and Nutrition Examination Survey NHANES (2013–2014). An 8-item odor identification test was applied to determine olfactory function. Muscle strength was determined through a handgrip dynamometer (defined as the sum of the largest handgrip strength reading from right and left hands). Moderation analysis was performed to test whether the association between age and olfactory impairment was moderated by handgrip strength. Moderation analysis highlighted two regions of significance: the first region was found at < 56.6 kg, indicating that the adverse influence of age on olfactory function may be greater for the participants in this area; the second region was found at ≥ 56.6 kg, indicating that the negative impact of age on olfactory function disappeared for adults who were above this estimate point. In conclusion, handgrip strength, a general indicator of muscle strength, moderates the relationship between age and olfactory ability in a US adult population aged 40 years and older. Our findings are clinically relevant, since they emphasize the importance of muscular fitness in adulthood and old age by diminishing the deleterious effect of aging on olfactory performance. © 2021, The Author(s).